Speech intelligibility after gingivectomy of excess palatal tissue - Aruna Balasundaram; Mythreyi Vinayagavel; Dhathri Priya Bandi (Wolters Kluwer Medknow Publications, 2014)
To appreciate any enhancement in speech following gingivectomy of enlarged anterior palatal gingiva. Periodontal literature has documented various conditions, pathophysiology, and treatment modalities of gingival enlargement. Relationship between gingival maladies and speech alteration has received scant attention. This case report describes on altered speech pattern enhancement secondary to the gingivectomy procedure. A systemically healthy 24-year- female patient reported with bilateral anterior gingival enlargement who was provisionally diagnosed as "gingival abscess with inflammatory enlargement" in relation to palatal aspect of the right maxillary canine to left maxillary canine. Bilateral gingivectomy procedure was performed by external bevel incision in relation to anterior palatal gingiva and a large wedge of epithelium and connective tissue was removed. Patient and her close acquaintances noticed a great improvement in her pronunciation and enunciation of sounds like "t", "d", "n", "l", "th", following removal of excess gingival palatal tissue and was also appreciated with visual analog scale score. Exploration of linguistic research documented the significance of tongue-palate contact during speech. Any excess gingival tissue in palatal region brings about disruption in speech by altering tongue-palate contact. Periodontal surgery like gingivectomy may improve disrupted phonetics. Excess gingival palatal tissue impedes on tongue-palate contact and interferes speech. Pronunciation of consonants like "t", "d", "n", "l", "th", are altered with anterior enlarged palatal gingiva. Excision of the enlarged palatal tissue results in improvement of speech.